اتجاهات رسائل الدراسات العليا في الجامعة اإلسالمية العالمية بماليزيا قسم الفقه وأصوله السنوات 1998 -2010 =Postgraduate thesis trends at the International Islamic University of Malaysia: Department of Jurisprudence and its origins, the years 1998-2010 =Kecenderungan Aliran Tesis Sarjana di Universiti Islam Antarabangsa Malaysia: Jabatan Fiqh dan Usul al-Fiqh, Tahun 1998-2010 - Bahjat, Munjid Mustafa; Akbar, Mohamed Aslam (IIUM, 2018)
This study documents a large number of Masters theses written by students of the International Islamic University Malaysia over 19 years from 1998 to 2016. A total of 282 Masters theses were written in the Arabic language during the aforementioned period. The main themes covered in the theses were identified by the researchers. The jurisprudence of transactions and Islamic finance were the two most prominent themesnwith 87 theses written (30% of all theses written in the 19 year period). Family jurisprudence came in second place with 63 theses (22% of all theses) followed in third place by Usuli studies and juristic maxims which were the main themes for 44 theses (15%). The fourth major theme was found to be crime and hudud with 23 theses written. The four aforementioned themes accounted for 75% of all Arabic Masters theses written between 1998 and 2016. Due to time and other constraints, the researchers were unable to carry out a comprehensive review of all theses written instead, the researchers focused on a total of 81 Masters theses written on the Jurisprudence of Transactions (40 theses) and Islamic finance (41 theses) written between 1998 and 2010. The aforementioned theses represented 49% of all theses written in the 12 year period. Emphasizing the importance of University theses during the process of writing literature reviews is an established norm that is attributed to the fact that such theses represent the latest developments in research. This study is expected to help future researchers locate relevant literature in the form of Masters theses and consequently carryout effective literature reviews. This inductive study does not represent a comprehensive review of all theses written between 1998 and 2010. However the researchers managed to document all theses written in the two aforementioned themes during the 12 year period.